STUDI FAKTOR RISIKO OSTEOPOROSIS PADA PEREMPUAN LANSIA DI KECAMATAN CIMANGGIS KOTA DEPOK TAHUN 2022 - Kunthi Ayu Kusumawardani, (2023)
Abstrack Osteoporosis is a disease characterized by damage of bone microarchitecture and decreased bone density. The prevalence of osteoporosis in the elderly worldwide is 21.7% and the highest prevalence is in Asia, 24.3%. Elderly women are four times more at risk of suffering from osteoporosis than elderly men. Osteoporosis is caused by multifactorial and has many risk factors. The elderly population in Indonesia continues to grow and contributes to the increasing incidence of osteoporosis. Osteoporosis can cause fractures which reduce quality of life and increase health costs. Therefore, a study was conducted to determine the influential risk factors and preventative measures can be taken. This study aims to determine the relationship between risk factors and osteoporosis in elderly women. The study was conducted using a cross-sectional design using consecutive sampling technique to 110 respondents and analyzed using chi-square. The results showed that the majority of the elderly suffer from osteoporosis (77.3%). IMT and parental history of hip fracture showed a significant relationship with bone density (p value 0.041 and 0.018). History of fractures after 50 years of age, height loss > 4cm, comorbidities, drug consumption > 3 months, smoking, alcohol consumption showed no significant relationship with bone density (p value 0.396, 1.00, 0.507, 0.279, 0.252, 0.174). Keywords: osteoporosis, risk factors, elderly, women, maternal fracture